1966
DOI: 10.1366/000370266774385994
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Magnesium and Aluminum Alloys by Atomic-Absorption Spectroscopy

Abstract: The application of atomic absorption spectroscopy to the analysis of magnesium alloys and scrap aluminum is described. Ca, Cu, Mn, and Zn are determined in Mg alloys, while Cu, Fe, Mg, and Zn in the alloy range are determined in the aluminum samples. In aluminum analysis, synthetic standards and a spiking procedure are employed to compensate for matrix effects. Comparison with chemical results shows AA (atomic absorption) to be a reliable analytical tool in these applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1968
1968
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…None of the ions studied here caused any interference except for a depression by a large (100-fold) excess of Mg. A 6-ppm solution of Mn showed 50.2% absorption; with the presence of 600 ppm of Mg, the absorption was 43.4%. This is probably a matrix effect due to high solids content; a chemical interference of this type was not previously noted (14). More than 500 ppm of AI slightly depressed, due to matrix effects (8) and a large excess (not a problem in this determination) of Cu caused a very slight enhancement of the absorption of zinc (15).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…None of the ions studied here caused any interference except for a depression by a large (100-fold) excess of Mg. A 6-ppm solution of Mn showed 50.2% absorption; with the presence of 600 ppm of Mg, the absorption was 43.4%. This is probably a matrix effect due to high solids content; a chemical interference of this type was not previously noted (14). More than 500 ppm of AI slightly depressed, due to matrix effects (8) and a large excess (not a problem in this determination) of Cu caused a very slight enhancement of the absorption of zinc (15).…”
Section: Resultsmentioning
confidence: 66%
“…Calibration plots for the major constituents of the ferrite compounds in question were determined each time data were taken, except for a few cases where two standards were used and unknowns were determined by direct proportion. The replicate determinations of these plots indicate that the practical upper limits of the six major elements under the conditions were used as follows: Fe, 15-18 ppm; Li, [12][13][14][15] ppm; Ni, 25 ppm; Mn, 15-18 ppm; Cu, 20 ppm; and Zn, 4-5 ppm. Deviations from Beer's law were noted at higher concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The organic extract was then analyzed by atomic absorption spectroscopy. When manganese was determined, the MIBK solution was analyzed immediately because the manganese-APDC complex is unstable in this solvent (9).…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…Literature survey revealed that simultaneous estimation of aluminium and magnesium was done by atomic absorption spectroscopy, 7,8 potentiometrically, 9 hydroxide co-precipitation, 10 complexometrically 11,12 and inductively coupled plasma optical emission spectroscopy. 13 The aim of the present work was to develop an inductively coupled plasma mass spectrometric method for the analysis of aluminium and magnesium using closed vessel microwave-assisted digestion and validate the method.…”
Section: Introductionmentioning
confidence: 99%